Map‐based cloning and functional analysis revealed ABCC2 is responsible for Cry1Ac toxin resistance in Bombyx mori. Issue 2 (20th March 2022) - Wang, Xin; Yi, Xiao‐li; Hou, Cheng‐xiang; Wang, Xue‐yang; Sun, Xia; Zhang, Zhong‐jie; Qin, Sheng; Li, Mu‐wang
Abstract: Bt toxins are parasporal crystals produced by Bacillus thuringiensis (Bt). They have specific killing activity against various insects and have been widely used to control agricultural pests. However, their widespread use has developed the resistance of many target insects. To maintain the sustainable use of Bt products, the resistance mechanism of insects to Bt toxins must be fully clarified. In this study, Bt‐resistant and Bt‐susceptible silkworm strains were used to construct genetic populations, and the genetic pattern of silkworm resistance to Cry1Ac toxin was determined. Sequence‐tagged site molecular marker technology was used to finely map the resistance gene and to draw a molecular genetic linkage map, and the two closest markers were T1590 and T1581, indicating the resistance gene located in the 155 kb genetic region. After analyzing the sequence of the predicted gene in the genetic region, an ATP binding cassette transporter ( ABCC2 ) was identified as the candidate gene. Molecular modeling and protein–protein docking result showed that a tyrosine insertion in the mutant ABCC2 might be responsible for the interaction between Cry1Ac and ABCC2. Moreover, CRISPR/Cas9‐mediated genome editing technology was used to knockout ABCC2 gene. The homozygous mutant ABCC2 silkworm was resistant to Cry1Ac toxin, which indicated ABCC2 is the key gene that controls silkworm resistance to Cry1Ac toxin. The results have laid the foundation for elucidating the molecular resistance mechanism of silkworms to Cry1Ac toxin and could provide a theoretical basis for the biological control of lepidopteran pests. Abstract : ABCC2 gene was identified as a Cry1Ac resistance‐related gene in Bombyx mori . Y234, an inserted amino acid in ABCC2 amino acid sequence, was considered as the key site for Cry1Ac resistance. Molecular modeling and docking results showed that this insertion impaired interactions between Cry1Ac and ABCC2. This result gives a new inspiration for understanding the Cry1Ac resistance in B. mori .